A systematic review of the effectiveness of non- health facility based care delivery of antiretroviral therapy for people living with HIV in sub-Saharan Africa measured by viral suppression, mortality and retention on ART - Limbada, Mohammed; Zijlstra, Geiske; Macleod, David; Ayles, Helen; Fidler, Sarah (BMC public health, 2021)
Background Alternative models for sustainable antiretroviral treatment (ART) delivery are necessary to meet the increasing demand to maintain population-wide ART for all people living with HIV (PLHIV) in sub-Saharan Africa. We undertook a review of published literature comparing health facility-based care (HFBC) with non-health facility based care (nHFBC) models of ART delivery in terms of health outcomes; viral suppression, loss to follow-up, retention and mortality. Methods We conducted a systematic search of Medline, Embase and Global Health databases from 2010 onwards. UNAIDS reports, WHO guidelines and abstracts from conferences were reviewed. All studies measuring at least one of the following outcomes, viral load suppression, loss-to-follow-up (LTFU) and mortality were included. Data were extracted, and a descriptive analysis was performed. Risk of bias assessment was done for all studies. Pooled estimates of the risk difference (for viral suppression) and hazard ratio (for mortality) were made using random-effects meta-analysis. Results Of 3082 non-duplicate records, 193 were eligible for full text screening of which 21 published papers met the criteria for inclusion. The pooled risk difference of viral load suppression amongst 4 RCTs showed no evidence of a difference in viral suppression (VS) between nHFBC and HFBC with an overall estimated risk difference of 1% [95% CI -1, 4%]. The pooled hazard ratio of mortality amongst 2 RCTs and 4 observational cohort studies showed no evidence of a difference in mortality between nHFBC and HFBC with an overall estimated hazard ratio of 1.01 [95% CI 0.88, 1.16]. Fifteen studies contained data on LTFU and 13 studies on retention. Although no formal quantitative analysis was performed on these outcomes due to the very different definitions between papers, it was observed that the outcomes appeared similar between HFBC and nHFBC. Conclusions Review of current literature demonstrates comparable outcomes for nHFBC compared to HFBC ART delivery programmes in terms of viral suppression, retention and mortality. PROSPERO number CRD42018088194 .